Uncertainty Representation and Reasoning in the Semantic Web - da Costa, P; Laskey, K; Lukasiewicz, T (2008)
This chapter is about uncertainty representation and reasoning for the Semantic Web (SW). We address the importance, key issues, state-of-the-art approaches, and current efforts of both the academic and business communities in their search for a practical, standard way of representing and reasoning with incomplete information in the Semantic Web. The focus is on why uncertainty representation and reasoning are necessary, its importance to the SW vision, and the major issues and obstacles to addressing uncertainty in a principled and standardized way. Although some would argue that uncertainty belongs in the \"rule layer\" of the SW, we concentrate especially on uncertain extensions of ontology languages for the Semantic Web.